Informal IGOs as Mediators of Power Shifts. (17th November 2020) - Vabulas, Felicity; Snidal, Duncan
Abstract: In an era defined by shifting distributions of power, states are not only pushing for change in formal international organizations, they are increasingly using informal intergovernmental organizations (IIGOs) to mediate change. Why and how do states use IIGOs – institutions without a treaty or secretariat – to manage global power shifts? IIGOs are useful for states on both sides of the power shift. Established powers use IIGOs for system management through 'collaboration' and strengthening the 'hegemonic consensus' to preserve their institutional privileges while adapting to changing power realities. Rising powers use IIGOs to redistribute through 'power bargaining' and 'rhetorical coercion' to strengthen their institutional roles without overly disrupting the current order. Established and rising powers also work together to use IIGOs for integrative strategies including 'cooptation' and 'principled persuasion', creating a mutually beneficial solution that accommodates both increased demands but also mounting responsibilities. IIGOs help states manage power transitions by providing flexible institutional arrangements that facilitate bargaining without freezing outcomes in permanent institutions while the power distribution evolves. We provide case vignettes of the G7 (system management) in the early phase of a power shift, BRICS (redistributive strategies) in the middle phase, and the G20 (integrative strategies) in the later phase. Abstract : IIGOs provide a propitious setting for states to adapt institutional arrangements to the evolving power distribution. Both challengers to and beneficiaries of the prevailing institutional distribution of power benefit from IIGOs during times of power shifts to avoid major institutional disruptions that would damage them all.